Mechanisms affecting the delayed efficiency of cement based stabilization/solidification processes. (10th July 2020) - Senneca, Osvalda; Cortese, Luciano; Di Martino, Raffaela; Fabbricino, Massimiliano; Ferraro, Alberto; Race, Marco; Scopino, Andrea
Abstract: The paper investigates the efficiency of a cement-based stabilization/solidification treatment conducted on a chromium-contaminated soil. The aim of the paper is to understand the main mechanisms responsible for metal immobilization, and to verify if delayed reactions, due to the presence of additives, may decrease the overall efficiency of the process. The study is conducted testing, as additives, either natural pozzolan and/or fly ashes. Used materials are chemically characterized, and analyzed through X-ray diffraction, thermogravimetric and differential scanning calorimetry analysis, and sequential extraction. Metal leaching experiments and water absorption tests are conducted on stabilized/solidified samples. Results obtained on cured specimens and six months after curing time are compared to verify the effect of delayed reactions. Obtained results indicate that the development of hydration reaction associated to alkaline conditions increases up to 10% the residual fraction of the metal, reducing its mobility (stabilization). The effect of solidification, due to metal incorporation in cement hydration products, gives an important contribution to the overall effectiveness of the process. The immobilization factor varies between 6 and 9%, and are therefore several folds higher than the expected values, estimated around 1%. The effectiveness decreases after curing, both in absence of additives, and in presence of fly ashes. In the first case, chromium release goes from 80 to 160 μg L −1 . In the second case it increases from less than 30 to more than 150 μg L −1 . X-Ray diffraction analysis and water adsorption tests suggest that the loss of efficiency is due to the delayed formation of ettringite, associated to the internal micro cracking of aged specimens, because metal release is mainly regulated by diffusion mechanisms. Graphical abstract: Image 1 Highlights: Pozzolanic additives increase short-term effectiveness of the process. Different additives have a different effect of delayed effectiveness of the process. Delayed ettringite formation is responsible for the reduction of process efficiency. High sulfate content in fly ashes increases the delayed ettringite formation risk.